CardioVilla 2011: congratulations to the health of cardiovascular medicine in Cuba - Raúl Dueñas Fernández; Alberto Morales Salinas; Rubén Tomás Moro Rodríguez; Jesús A. Satorre Ygualada (Revista Finlay)
In this editorial, some of the most relevant issues dealt with in CardioVilla IV Cardiac Congress 2011 are presented. This congress was held in Santa Clara, Cuba, from October 13th to 15th, 2011. It was sponsored by several scientific societies, including the American Society of Cardiology. A video conference was organized with the representatives of this society. At the conference, the 25th anniversaries of Cardiology Centers Saturmino Lora, William Soler and Ernesto Che Guevara were commemorated. In addition, the new Board of Directors of the Cuban Society of Cardiology was elected.